The Impact of Indonesia's Mining Industry Regulation on the Protection of Indigenous Peoples - Mohammad Jamin; Abdul Kadir Jaelani; Mulyanto Mulyanto; Reza Octavia Kusumaningtyas; Duc Quang Ly (Faculty of Law, Hasanuddin University, 2023)
The government has established various policies regarding mining in Indonesia. Still, an important question that needs to be asked is whether these policies have provided benefits, justice, and balance for indigenous and tribal peoples. This study aims to analyze the impact of Indonesian mining regulations on the protection of indigenous peoples. This is a normative legal research effort. The literature review gathers information from document analysis, which is analyzed qualitatively. Data analysis is descriptive-analytic in nature. The study results show that the impact of mining regulations still needs to reflect the recognition and protection of the rights of indigenous peoples. There is a need to improve mining management legislation and systems. Standardization of reclamation and post-mining management is required to provide implementation guidelines that meet the needs of the community. It has no negative impact on the community surrounding the mine. Licensing is one policy that can be used to implement standardization, which means keeping an eye on how the land is managed after mining, how waste is handled, and how policies are made to encourage mining and conservation activities that are good for the environment.